2019
DOI: 10.11591/ijeecs.v14.i1.pp333-339
|View full text |Cite
|
Sign up to set email alerts
|

Comparing bags of features, conventional convolutional neural network and AlexNet for fruit recognition

Abstract: This paper presents a comparative study between Bag of Features (BoF), Conventional Convolutional Neural Network (CNN) and Alexnet for fruit recognition.  Automatic fruit recognition can minimize human intervention in their fruit harvesting operations, operation time and harvesting cost.  On the other hand, this task is very challenging because of the similarities in shapes, colours and textures among various types of fruits. Thus, a robust technique that can produce good result is necessary. Due to the outsta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The three fully-connected layers, each hosting 4096 neurons, play a vital role in object categorization, while the final SoftMax layer predicts object classes in the images. This architectural design, coupled with specified filter sizes, has become a cornerstone in the field of deep learning [41,42]. The entire course of this study is depicted in Figure 5.…”
Section: Classification Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The three fully-connected layers, each hosting 4096 neurons, play a vital role in object categorization, while the final SoftMax layer predicts object classes in the images. This architectural design, coupled with specified filter sizes, has become a cornerstone in the field of deep learning [41,42]. The entire course of this study is depicted in Figure 5.…”
Section: Classification Methodsmentioning
confidence: 99%
“…We acquired the trained models after the training procedure was finished. The trained model was then used to classify the test dataset [42].…”
Section: Classification Methodsmentioning
confidence: 99%
“…It mainly scans this input image. It then generates k output boxes, all with two scores representing probability for an object's availability [16], [17]. Figure 1 depicts the F-RCNN architecture.…”
Section: Architecture Of F-rcnnmentioning
confidence: 99%
“…The article [14] presented a comparative study between Bag Of Features (BOF), Conventional Convolutional Neural Network (CNN), and AlexNet for fruit recognition. The results indicated that all three techniques had excellent recognition accuracy, but the CNN technique was the fastest at presenting a recognition prediction.…”
Section: Related Workmentioning
confidence: 99%